Desenvolvimento de um instrumento para avaliação da força labial e modelagem computacional do músculo orbicular da boca - Tatiana Vargas de Castro Perilo (2012)
The orbicularis oris muscle, which constitutes the human lips, actively participates in significant functions such as sucking, mastication, swallowing, speech, breathing, and facial mimic. The principal aim of this study was to develop a device for measuring the lip force and for specifics aim to development a computer model for the orbicularis oris. For building this device, a mechanical system was designed and manufactures using fast prototyping, composed by four intraorallypositioned pieces. Four FlexiForce sensors were used for building the electronic system. The system for signal conversion, amplification, and transmission was elaborated, with the data collection being done by a PIC microcontroller with USB interface and the signal storage being done in a microcomputer. After the device calibration, 40 females subjects between 20 and 33 years of age (mean of 24.3) presenting closed lip habitual postural were evaluated. Three consecutive measurements of maximal lip force were performed, with contraction time of seven seconds and one-minute interval between tests. The obtained data was analyzed using the statistical software R, version 2.11, considering a significance level of 5%. Magnetic resonance images of the orbicularis oris of a healthy 27-year-old female subject were used for building the computerized model. Mimics was used for building the geometric model, which was validated by comparison with anthropometric measurements performed in vivo. The muscular behavior model was obtained fromprevious studies and applied in the finite element software ABAQUSÔ. Mean labial force values from 3.45 N to 29.96 N were found, with average of 13.27 N, and higher values were found for the upper lip force (7.33 N), when compared to the lower lip force (5.94 N). Statistical similarity wasobtained in the values obtained in the three lip force measurements consecutively performed in the same participant.